2013
DOI: 10.1016/j.resp.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreceptors, baroreceptors, and autonomic deregulation in children with obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is highly prevalent sleep disorder of breathing in both adults and children that is fraught with substantial cardiovascular morbidities, the latter being attributable to a complex interplay between intermittent hypoxia (IH), episodic hypercapnia, recurrent large intra-thoracic pressure swings, and sleep disruption. Alterations in autonomic nervous system function could underlie the perturbations in cardiovascular, neurocognitive, immune, endocrine and metabolic functions that affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 142 publications
(156 reference statements)
1
28
0
Order By: Relevance
“…Rodent models of long-term intermittent hypoxia have demonstrated hypertension and increased sympathetic activity (22), increased right ventricular systolic pressure, right ventricular mass, neovascularization of distal pulmonary vessels (23), systemic and pulmonary vascular pressure (24,25), cardiac hypertrophy, and cardiac and perivascular fibrosis (26). Previous studies in children have however not found a strong link between arterial desaturation and elevated HR and BP (27). Similarly in our study, oxygen desaturation Figure 2.…”
Section: Repetitive Respiratory Events In Childrensupporting
confidence: 81%
“…Rodent models of long-term intermittent hypoxia have demonstrated hypertension and increased sympathetic activity (22), increased right ventricular systolic pressure, right ventricular mass, neovascularization of distal pulmonary vessels (23), systemic and pulmonary vascular pressure (24,25), cardiac hypertrophy, and cardiac and perivascular fibrosis (26). Previous studies in children have however not found a strong link between arterial desaturation and elevated HR and BP (27). Similarly in our study, oxygen desaturation Figure 2.…”
Section: Repetitive Respiratory Events In Childrensupporting
confidence: 81%
“…Thus, the recurrent hypoxemic events and the episodic arousals that characterize sleep in patients with OSA likely enhance sympathetic tonic outfl ow, and result in increased recovery of catecholamines in the urine. 4 Taken together, we surmise that the changes in evening-to-morning epinephrine and norepinephrine levels are probably better suited for detection of OSA and the response to specifi c therapeutic interventions for pediatric OSA. Notwithstanding, the individual ROCs for overnight changes in urinary catecholamine levels were not suffi ciently adequate predictors of OSA to enable their use as single biomarkers.…”
Section: Discussionmentioning
confidence: 78%
“…As in adults, OSA in children leads to sympathetic nervous system activation, increased heart rate variability, and increased catecholamine production,295,355,405,412414 which likely underlie many of the associations between OSA and blood pressure in children 415. Oxidative stress in children with OSA relating to IH has been found to increase lipid peroxidation, which can accelerate atherosclerosis.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%